Social Criticism through Ghost Storytelling on Tirto.id Podcast Contents - Razali, Geofakta; Wirawan, Wirawan (Universitas Nusa Cendana, 2024)
This research aims to identify the pattern of ghost storytelling in podcasts produced by Tirto.id journalists. It attempts to answer the question whether ghost storytelling on the Tirto.id podcast channel is a means of audience entertainment or whether it truly reflects the function that journalists play in educating the public and actualising societal criticism. Implementing a qualitative content analysis method, this study explores five ghost episodes on Tirto.id’s INSENTIF podcast channel. We argue that the selected podcast episodes exemplify the hybridity of journalism which amalgamates information with elements of fiction. We conclude that these podcast episodes on ghosts serve a deeper purpose than just telling stories about ghosts. They aim to entertain the audience while subtly engaging them in discussions surrounding social issues, such as patriarchy, parental love, relationships, and colonialism. This study supports Baym’s idea to perceive journalism as orientation, rather than just as information.